The Contribution of Corporate Governance in Increasing the Financial Performance of Family Businesses: a Study on a Sample of Family Companies From Oum el Bouaghi and Batna Provinces. - Benzouai, Mehamed Cherif; Hella, Lilia (Journal of Human Sciences, 2023)
This study aims to explore the impact of corporate governance on financial performance of family companies. Through identifying the basics of corporate governance and financial performance. Also, to highlight the role of corporate governance in family companies management and to ensure its sustainability and growth. We choose a purposive sample family companies from Oum El Bouaghi and Batna provinces for the year 2018. A descriptive approach was followed to show concepts that are related to corporate governance, in addition to analytical-statistical approach which is used to measure the impact of corporate governance on  financial performance of family companies. Ordinaire least squares method was used to estimate a regression model in order to measure the impact of governance on financial performance.The study concluded that there is no relationship between corporate governance and financial performance in family companies in Oum  El Bouaghi and Batna provinces, and one of the most important recommandations of this study is that family companies should not give much importance to corporate governance, since the agency problem that it face is weak.